FACTORS AFFECTING MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) REVENUE OF PEOPLE’S BUSINESS CREDIT (KUR) RECEIVERS IN DONGGALA REGENCY - Ary Widdodo; Rustam Abd Rauf; Lien Damayanti (Tadulako University, 2016)
This research aims to determine the factors affecting micro small and medium enterprises (MSMEs) revenue of people’s business credit (KUR) receivers in Donggala Regency. Factors that allegedly influenced the income of MSMEs of KUR recipients include turnover, length of business, number of manpower and number of KUR.This research was conducted in December 2016 until January 2017 in Donggala Regency. The number of samples used are 43 debtors from Bank Nasional Indonesia (BNI), Bank Rakyat Indonesia (BRI) and Bank Mandiri. The sample is using snowball sampling method, and the data analyzed using Multiple Linear Regression Analysis. Based on the analysis result, it can be concluded that the factors that influence the revenue of MSMEsof KUR receiver are the turnover, the number of labor and the KUR number while the old factor of business does not affect the revenue of MSMEs receiving KUR